Teacher Obstacles in Thematic Learning Implementation Based on the 2013 Curriculum - Faishol, Riza; Wong-A-Foe, Daphne; Abdullah, Abdullah; Nurhakim, Nova; Habibi, Riki; Hajar, Siti; Nasrodin, Nasrodin; Fauzi, Anis; Sofa, Ainur Rofiq (FKDP (Forum Komunikasi Dosen Peneliti), 2025)
This study aims to analyze the obstacles faced by teachers in the implementation of thematic learning based on the 2013 curriculum at MI Al-Aziz. The research focuses on three key areas: (1) the implementation of thematic learning, (2) the challenges encountered by teachers, and (3) solutions to overcome these obstacles. The study employs a qualitative descriptive approach, using observation, interviews, and questionnaires as primary data collection methods. The results indicate that the thematic learning implementation has not been fully optimal due to a lack of teacher preparedness in lesson planning, limited resources, and inadequate training. Teachers also face difficulties in integrating various subjects into a coherent thematic approach. The study suggests that improving teacher training and providing better resources can enhance the implementation of the curriculum and resolve existing challenges.